The River Flows On : Black Resistance, Culture, and Identity Formation in Early America - Rucker, Walter C., 1970- (Book collections on Project MUSE., 2006)
"The River Flows On is broad study of slave resistance in America, spanning the colonial and antebellum eras in both the North and South and covering all forms of recalcitrance, from major revolts and rebellions to everyday acts of disobedience. Walter C. Rucker analyzes American slave resistance with a keen understanding of its African influences while he also traces the emergence of an "African American" identity, orientation, consciousness, and culture."--Jacket.